2012
DOI: 10.1177/0969776412459860
|View full text |Cite
|
Sign up to set email alerts
|

The eventification of place: Urban development and experience consumption in Berlin and New York City

Abstract: Recent urban and economic development policies put much emphasis on the promotion of experiences. Within the experience economy, the production and consumption of products and places is transformed into “theater.” The organization of international festivals highlights that trend. However, festivalization has also infiltrated urban and economic development on a much smaller scale and turned into an overall eventification. In addition, producers and marketers of cultural products simultaneously apply this concep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(48 citation statements)
references
References 35 publications
0
44
0
4
Order By: Relevance
“…The relevance of urban events is nowadays significant enough to give rise to a new modality of production of space (Lefebvre, 1992): the "eventification of places" (Jakob, 2012) or "eventalisation of urban space" (Pløger, 2010). As whatever production of space, lived ("eventified") spaces result from the intersection between perceived and conceived spaces (Purcell, 2003): the material settings experienced and perceived during events and the variety of representations and narratives by which events are used to valorize the urban space (Pavoni, 2011).…”
Section: Practicing a Right To The City Through Participating In Eventsmentioning
confidence: 99%
See 2 more Smart Citations
“…The relevance of urban events is nowadays significant enough to give rise to a new modality of production of space (Lefebvre, 1992): the "eventification of places" (Jakob, 2012) or "eventalisation of urban space" (Pløger, 2010). As whatever production of space, lived ("eventified") spaces result from the intersection between perceived and conceived spaces (Purcell, 2003): the material settings experienced and perceived during events and the variety of representations and narratives by which events are used to valorize the urban space (Pavoni, 2011).…”
Section: Practicing a Right To The City Through Participating In Eventsmentioning
confidence: 99%
“…These features are typical of a variety of events, with different goals, contents and spatial scales: although the relevance of the political-economic interests and actors involved foreground mega-events, scholars increasingly recognize that the diffusion of events has infiltrated urban development on a much smaller scale (Quinn, 2005). The comparative study of Wedding neighborhood in Berlin and South Bronx of New York shows that in both cases urban events organized by local artists and civil society actors directly affect the urban development of these areas, provoking gentrification and the exclusion of the most marginal local population (Jakob, 2012;Zukin, 1995).…”
Section: Practicing a Right To The City Through Participating In Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…Falamos, por exemplo, no aumento das rendas e do custo de vida nas áreas das cidades onde proliferam estes eventos, por norma as suas zonas centrais, que ao extremo podem encetar processos de gentrificação, de recomposição sociodemográfica e exclusão socioeconómica, através do afastamento dos segmentos mais frágeis da população destas áreas da cidade. Autores como Jakob (2013), que têm vindo a analisar esta tendência para a "eventificação" ou "eventualização" das cidades, reforçam a necessidade de adopção de estratégias mais equilibradas e orientadas para os actores locais, para que não seja posta em causa a identidade de determinados bairros ou zonas das cidades em prol de tendências homogeneizadoras. Se a população local e os segmentos populacionais mais desfavorecidos continuarem a ser ignorados por estas estratégias, continuarão também a ser excluídos de todos e quaisquer benefícios que delas possam advir.…”
Section: Reflexosunclassified
“…The enquiry made by the municipality showed that the three most common statements were that (1) the parking must go, (2) the king must go (the statue), and (3) that the square should be a place of events (Andersson and Göransson, 2008, p. 3). The inhabitants of Malmö as well as the planners seem to agree that Stortorget is a place associated with events, and this territorial association also dominated the directions of the competition program considering the redesign of the square proposed in 2009 (Göransson, 2009;see Pløger, 2010, andJakob, 2013, on the eventification of cities).…”
Section: Territorial Associationsmentioning
confidence: 99%